Pengaruh Gaya Hidup, Suasana Cafe dan Kualitas Pelayanan Terhadap Keputusan Pembelian “Dalam Rasa Kopi” di Setu Bekasi - Bagas Mulyadi; Novita Wahyu Setyawati; Franciscus Dwikotjo Sri Sumantyo (Inovan Publisher, 2025)
The purpose of this study was to understand the impact of Lifestyle, Cafe Atmosphere, and Service Quality on Purchasing Decisions. This study used a quantitative methodology with a purposive sampling technique. The population in this study were all visitors to the “Dalam Rasa Kopi” cafe, 102 respondents. The results showed that the lifestyle variable had a significant positive effect on purchasing decisions. On the other hand, the cafe atmosphere variable did not show a significant effect on purchasing decisions. In addition, the service quality variable also had a partial positive effect on purchasing decisions.